Mathematics teachers attitudes towards the use of e- learning in teaching mathematics to middle school students under the Corona pandemic (Journal of the College of Basic Education, 2022)
The research aims to identify the attitudes of mathematics teachers towards the use of e-learning in teaching mathematics to middle school students in light of the Corona pandemic, as well as knowing the differences between the attitudes of mathematics teachers towards e-learning that are attributed to the gender variable. A paragraph after reviewing previous studies that dealt with the same topic. The study population consisted of (196), while the sample numbered (50) male and female teachers of mathematics. The researcher also adopted the statistical program (Spss) in data processing. The search resulted in the following conclusions:1- The results of this study showed that the attitudes of mathematics teachers towards e-learning were in the neutral direction towards e-learning.2- The results also showed that there were no differences between the averages of mathematics teachers' attitudes towards e-learning in teaching mathematics according to the gender variable. This indicates that the gender variable has no effect on mathematics teachers' attitudes towards e-learning.The recommendations made by the research were as follows:1- Training the faculty to use and employ e-learning in the educational process through the establishment of training courses.2- Shedding light on e-learning by educational institutions in Iraq and the interest in employing it in the educational process and encouraging faculty to use it, as well as providing the appropriate educational infrastructure for the process of applying e-learning in schools, as well as providing physical facilities and preparing schools by equipping them with appropriate electronic media.